Degasification possibilities evaluation in Socotá coal mines (Boyacá, Colombia) - Mariño-Martínez, Jorge Eliécer; Ortegón-Cuéllar, Marco Tulio; Mariño-Santos, Natalia (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In the Socotá area in Boyacá, Colombia, high contents of coalbed methane have been reported. In order to prove it, additional gas measurements were done and different possibilities of degassing were considered. To measure the gas content, the canisters desorption system were used, with control of pressure and temperature, according to the USBM and GRI methodology. Lost, desorbed and residual gases were determined separately, and proximate analyses were also carried out. In some samples the content of gas reached the 100-200 SCF/t. These gas contents have good possibilities for energy production (CBM) by drilling vertical wells to extract it.Those wells would not only produce gas, but would also degas the future underground mining areas. The combination of degasification and ventilation would considerably allow a decrease in the explosions risk. The high coalbed methane content in the area could produce energy for the mining company or commercial gas for the natural gas distribution network. The Socotá area has the ideal conditions for a pilot project, which could be a model for other degasification projects in Colombia.